Effects of revenue from tourism on Montenegro's balance of payments - Veličković Maja R.; Tomka Dragica (University Educons, Faculty of Sports and Tourism, Novi Sad, 2017)
Tourism is one of the most important industries in Montenegro, having several multiplier effects. Direct contribution of tourism to economic growth and development of Montenegro became even more important in the period after the outbreak of the global economic crisis. Due to low export competitiveness and high dependence of its economy on import, Montenegro has been facing high deficit in foreign trade and balance of payments for years. The article aims to analyze the trend of revenue from foreign tourists and to assess the effects of such revenue on overall changes to the current account of Montenegro's balance of payment. The results of the study show that in the period from 2008 onwards, growth of tourism revenue has lead to increased deficit in balance of payments. Since needs of tourists cannot be met from own sources, Montenegro has increased import of goods and services in the same period, which reduced total effects of tourism. In the years after the outbreak of the global economic crisis, the direct influence of tourism on increased surplus on the services subaccount within the current account of the balance of payments becomes even more important. Growth of tourism revenue leads to significantly higher surplus in the services subaccount, and therefore reduces the balance of payments deficit. Negative effects of tourism on goods import have been significantly reduced over the period, which allowed for a higher degree of coverage of trade deficit by tourism revenue. Increased revenue from foreign tourists at the same time causes higher growth of revenues from transport services, which has indirect positive effect on general changes in the current account of Montenegro's balance of payments.